Development of CMIP6‐Based Climate Scenarios for Japan Using Statistical Method and Their Applicability to Heat‐Related Impact Studies. Issue 11 (22nd November 2022) - Ishizaki, Noriko N.; Shiogama, Hideo; Hanasaki, Naota; Takahashi, Kiyoshi
Abstract: Climate scenario data set are indispensable for assessing future climate impacts. In this study, we developed statistically downscaled climate scenarios in Japan using modified bias correction method based on five general circulation models selected from the Coupled Model Intercomparison Project (CMIP) Phase 6 to facilitate impact assessments and adaptation strategies. Modification of time window of the original correction method results in successful agreement with the observed seasonal change of variables in each grid. The original CMIP6 models have a relatively small bias compared to CMIP5 models. The advantage of CMIP6‐based bias‐corrected scenarios is its availability for multiple global circulation models, which covered wide uncertainty in CMIP6 ensembles, with various emissions scenarios for representative concentration pathway (RCP) including RCP4.5, RCP2.6, and RCP8.5. Several temperature‐related indices derived from the CMIP6‐based climate scenarios agreed well with observations. The number of extremely hot days and nights increased nonlinearly in the future with additional global warming. An increase in the global warming level from 1 to 2°C above the early 1900s would increase the probability of the number of extremely hot days per year exceeding the 2018 case by 4.1 times. The development of bias‐corrected climate scenarios facilitates the study of various climate impacts on a CMIP6 basis. Plain Language Summary: It is important to appropriately remove model biases since the impact of climate change does not always depend linearly on the climate input data. To facilitate impact assessment based on the latest data set from CMIP6, we developed bias‐corrected daily climate scenarios for eight variables using five models. The application of climate scenarios to heat mortality‐related indices showed that they reproduced historical values well and would be useful for future projections. Key Points: We developed a statistically downscaled climate scenario in Japan based on five general circulation models selected from the Coupled Model Intercomparison Project Phase 6 to facilitate impact assessments Similar increasing trend was found for the temperature and precipitation between CMIP5‐ and CMIP6‐based climate scenarios, while CMIP6‐based scenario showed smaller biases for the underlying global circulation model. Addition of the moderate emission scenario for CMIP6‐based scenario enable us to consider wider range of the possible future Several threshold‐based indices derived from the climate scenarios was evaluated. They agreed with the observed values for the historical period. For the future, we can discuss the possible future change of indices in comparison with the historical values. Development of the bias‐corrected climate scenarios has enabled the broader impact assessment community in Japan to study various climate impacts on a CMIP6 basis